Electrocoagulation treatment of raw landfill leachate using iron-based electrodes: Effects of process parameters and optimization. (15th December 2017) - Huda, N.; Raman, A.A.A.; Bello, M.M.; Ramesh, S.
Abstract: The main problem of landfill leachate is its diverse composition comprising many persistent organic pollutants which must be removed before being discharge into the environment. This study investigated the treatment of raw landfill leachate using electrocoagulation process. An electrocoagulation system was designed with iron as both the anode and cathode. The effects of inter-electrode distance, initial pH and electrolyte concentration on colour and COD removals were investigated. All these factors were found to have significant effects on the colour removal. On the other hand, electrolyte concentration was the most significant parameter affecting the COD removal. Numerical optimization was also conducted to obtain the optimum process performance. Under optimum conditions (initial pH: 7.73, inter-electrode distance: 1.16 cm, and electrolyte concentration (NaCl): 2.00 g/L), the process could remove up to 82.7% colour and 45.1% COD. The process can be applied as a pre-treatment for raw leachates before applying other appropriate treatment technologies. Graphical abstract: Highlights: Electrocoagulation was used to treat raw landfill leachate. The effects of inter-electrode distance, pH and electrolyte were investigated. Process optimization was conducted using response surface methodology. All the 3 parameters have significant effects on the process performance. Up to 82.7% and 45.1% colour and COD removals were achieved.